Meningkatkan Hasil Belajar PKn Melalui Penerapan Model Pembelajaran TGT di SD Negeri Dawung, Tegalrejo, Magelang - Sulastri, Sulastri (Prosiding University Research Colloquium, 2021)
This study was used to determine the impac of using the TGT type of cooperative learning model in increasing interest in civics learning. The method used by the author in this study is a classroom action research method, with the subject of class II students at SD Negeri Dawung, Tegalrejo, Magelang with a population of 11 student where sample is taken from all students. This reserch was conducted with a cycle of planning, implementation and observation which ended with reflection and the continued by holing deliberations between members of the collaboration to determine planning and the next cycle. The instrument used for data collection is through multiple choice questions as many as 20 questions, the material used is the values of Pancasila. With the result that the use of the TGT (Teams Games Tournament) learning model can improved student learning outcomes.